Improving Communication During Cardiac ICU Multidisciplinary Rounds Through Visual Display of Patient Daily Goals*. Issue 7 (July 2016) - Justice, Lindsey B.; Cooper, David S.; Henderson, Carla; Brown, James; Simon, Katherine; Clark, Lindsey; Fleckenstein, Elizabeth; Benscoter, Alexis; Nelson, David P.
Abstract : Objectives: To improve communication during daily cardiac ICU multidisciplinary rounds. Design: Quality improvement methodology. Setting: Twenty-five–bed cardiac ICUs in an academic free-standing pediatric hospital. Patients: All patients admitted to the cardiac ICU. Interventions: Implementation of visual display of patient daily goals through a write-down and read-back process. Measurements and Main Results: The Rounds Effectiveness Assessment and Communication Tool was developed based on the previously validated Patient Knowledge Assessment Tool to evaluate comprehension of patient daily goals. Rounds were assessed for each patient by the bedside nurse, nurse practitioner or fellow, and attending physician, and answers were compared to determine percent agreement per day. At baseline, percent agreement for patient goals was only 62%. After initial implementation of the daily goal write-down/read-back process, which was written on paper by the bedside nurse, the Rounds Effectiveness Assessment and Communication Tool survey revealed no improvement. With adaptation of the intervention so goals were written on whiteboards for visual display during rounds, the percent agreement improved to 85%. Families were also asked to complete a survey (1–6 Likert scale) of their satisfaction with rounds and understanding of daily goals before and after the intervention. Family survey results improved from a mean of 4.6–5.7. Parent selection of the best possible score for each question was 19% at baseline and 75% after the intervention. Conclusions: Visual display of patient daily goals via a write-down/read-back process improves comprehension of goals by all team members and improves parent satisfaction. The daily goal whiteboard facilitates consistent development of a comprehensive plan of care for each patient, fosters goal-directed care, and provides a checklist for providers and parents to review throughout the day.